Pelaksanaan Program Perencanaan Persalinan dan Pencegahan Komplikasi - Mangampe, Novika; Hidayat, Asri (Journal of Telenursing (JOTING), 2024)
This study aims to determine the implementation of birth planning and prevention of complications. The method used is adapting the Arksey and O'Malley framework with five stages, namely identifying research questions, relevant studies, selecting subjects, mapping data, compiling, summarizing and reporting the results in the PubMed, Science Direct, Wiley databases and the Google Scholar web search engine. The research results showed that there were 16 articles related to the implementation of P4K. In conclusion, most of the prevalence has shown good implementation of P4K. Keywords: Prevention of jumps, planning, childbirth